ZORA 152: Slovene Women Writers at the Beginning of the 20th Century - Jensterle Doležal, Alenka (2023)
The monograph Slovene Women Writers at the Beginning of the 20th Century consists of eleven literary studies and an appendix containing biographies of the authors. This comparative research focuses on Slovene female authors at the beginning of Slovene modernism (the so-called “moderna” period). This monograph attempts to bring into focus forgotten female Slovene writers from this period, thus offering a critical view into the creations of Slovenian female authors of the “moderna” era (with reference to the broader fin-de-siècle period). This monograph focuses on the work of four key Slovene female authors of the “moderna” period: female prose writer and feminist Zofka Kveder (1878–1926) and the female poets Vida Jeraj (1875–1932), Ljudmila Poljanec (1874–1948), and Lili Novy (1885–1958). The book thus brings new insights into Slovene and Central European studies and comparative literary history, as well as spreading knowledge about the literary works of Slovene female authors in the wider scientific space.
Keywords: Slovene literature; Slovene women writers; Zofka Kveder; Vida Jeraj; Ljudmila Poljanec; Lili Novy